Prediction of Respiration Measurement Based on Temperature Differences of Fresh Strawberry (Fragaria x Ananassa var. Kelly Bright) in a Tropical Environment - Rizky, Widha Mutiara; Pamungkas, Agung Putra; Falah, Mohammad Affan Fajar (PLANTA TROPIKA, 2024)
Strawberry is a high-economic-value horticultural product that can be cultivated in tropical areas like Indonesia. Horticultural products retain their metabolism after harvest, such as respiration, which is an indicator of the degradation of products during storage. This study aimed to determine the best equation for predicting the respiration of strawberries cultivated using hydroponics in a greenhouse in Cangkringan, Yogyakarta. The respiration rate during storage was measured using an oxygen meter (DO-5510, Lutron, Taiwan) and a carbon dioxide meter (GH-2018 model, Lutron, Taiwan) in a closed system using an acrylic closed chamber. Five types of Michaelis-Menten equations were chosen as the best type based on R². The Arrhenius equation was used to get the highest value of R2 to predict the effects of temperature on respiration. Statistical analysis was used to determine the impact of treatments on the respiration rate. Based on the Arrhenius equation, the respiration of strawberries on postharvest in tropical environments depended on temperature. The best type for predicting the respiration of strawberries using the Michaelis-Menten mathematical model is competitive with an R2 value of 0.88. Therefore, the appropriate postharvest treatment is essential to add carbon dioxide or reduce oxygen levels.